Owning your message: Congressional candidates' interactivity and issue ownership in mixed-gender campaigns. Issue 2 (3rd April 2019) - Meeks, Lindsey
ABSTRACT: When candidates lose, they must decide which campaign strategies to keep and which to abandon if they run again. Republicans Mia Love and Scott Brown had to make this decision after losing in 2012 and running again in 2014. This study examines Love, Brown, and their Democratic opponents to assess how they changed and potentially optimized their Twitter strategies in back-to-back mixed-gender elections. Results revealed two patterns. First, textual and visual interactivity were prevalent campaign strategies. Second, effective campaign strategies incorporated issue emphases that aligned with the candidate's party- and/or gender-based political ownership, while simultaneously complimenting the nation's economic conditions.